Linguistic effects on the processing of two-digit numbers - Ganayim, D; Ganayim, S; Dowker, A; Olkun, S (Scientific Research Publishing, 2020)
The syntactic structure of numbers in Arabic mainly differs from that of Hebrew in terms of the order of units and decades. In Arabic (inverted), two-digit numbers are written and read from right to left, i.e. the first digit is the units and the second is the decades (24 = four and twenty), while in Hebrew (non-inverted), the reverse. Therefore, studying transcoding in the two languages may enable us to tease out the relative effects of linguistic experience (first versus second language) and counting system transparency i.e. the syntactic representation of numbers (inverted versus non-inverted number system). For this purpose, the paradigm of reading and writing two-digit numbers from dictation, in both languages was used. Sixty university bilingual students were given two tasks in both Arabic-L1 (First language) and Hebrew-L2 (Second language): One task involved writing two-digit numbers to dictation, and the other involved reading two-digit numbers aloud. Reading times and the error rates were calculated in both languages according to type of error—total errors, substitution errors (replacement of two-digit number units with decades, and vice versa; for example, 23 » 32), change errors (change of one digit 23 » 28), and omission errors (omission of one digit; for example 23 » 2). The participants made some errors in reading and especially in writing two-digit numbers. Their commonest errors were substitution errors compared to change and omission errors. Such errors were commoner for numbers which require processing the numerical syntactic structure than for decade numbers, or numbers from 11 to 19, which require less attention to numerical syntax. Speed and accuracy are greater in Arabic-L1 than Hebrew-L2, although the Arabic counting system has the inversion feature, and is thus less transparent than Hebrew. It is concluded that familiarity with the verbal counting system of the first language has a greater influence on transcoding than the transparency of the counting system. Theoretical and practical implications are discussed.